Training wall effects on power generation of tidal stream turbine arrays placed at headlands - Schnabl, A; Adcock, T; Houlsby, G (Technical Committee of the European Wave and Tidal Energy Conference, 2017)
Headlands are amongst the most promising features for potential tidal energy extraction sites, but the flow is significantly yawed with respect to the array plane. It has been suggested that guiding the flow has a positive impact on turbine loading and power production for this type of flow [1] [2]. This paper explores the effect of guiding the flow with training walls on power generation of a tidal turbine array at an idealised headland case [3] and a real site geometry, the Anglesey Skerries site, with realistic bathymetry and oscillating flow. The open-source code DG ADCIRC is used to solve the depth-averaged shallow water equations (SWEs) and a Linear Momentum Actuator Disc Theory (LMADT) model represents the turbines [4]. A parameter study is undertaken with the idealised headland site for both steady (constant flow rate) and unsteady flow conditions (sinusoidal water elevation). The parameters investigated in the study include shape, length, and angle of the training wall. Differences between steady and unsteady cases are explored for a range of flow rates (steady), frequencies and amplitudes (unsteady). The most favourable configurations are implemented in the real site simulation and compared to previous results without training walls.